E?cacy of Intrathecal Neostigmine with Intrathecal Dexmedetomidine in Postoperative Analgesia - Nischala Reddy G; Ajay Babu Ramakrishnan; S. Ankalagowri Sankardevar; Uthkala B Hegde (Academia Anesthesiologica International, 2020)
Background: The present study was conducted to compare the efficacy of intrathecal neostigmine with intrathecal dexmedetomidine in postop- erative analgesia. Subjects and Methods: The present study was conducted in the department of Anesthesia involving 100 patients belonging to ASA grade I and II, posted for elective Sub umbilical surgeries, under spinal anaesthesia. Group I patients received 3.0ml of hyperbaric solution of 0.5% bupivacaine + 50mcg (0.5ml) of Neostigmine. Group II patients received 3.0ml of hyperbaric solution of 0.5% bupivacaine + 10mcg (0.5ml) of dexmedetomidine. Results: The maximum patients were seen in age group 18-30 years ie 10 in group I and 16 in group II and minimum in 41-50 years ie 6 in group I and 4 in group II. The mean time for onset of sensory block in group I was 1.43 0.53 min and in group II was 2.319 0.44 min. The mean time for onset of peak sensory block in group I was 5.48 0.43 min and Group II was 7.31 0.44 min. Time for two segment regression was significantly higher in dexmedetomidine group as compared to neostigmine group, the mean time for two segment regression in group I was 124.98 21.48 min and group II was 165.24 14.45 min. The mean time for onset of motor block was 3.079 0.44 min in group I and 4.0454 0.38 min in group II. The mean duration of motor block in group I was 191.58 26.81 min and 324 36.8 min in group II. The difference was significant (P< 0.05). The mean sedation score in group I was 1.03 and in group II was 2.07. The difference was significant (P< 0.05). Conclusion: Authors recommend the use of dexmedetomidine as an adjuvant to bupivacaine in subarachnoid block